The effect on plasma prolactin levels of interictal epileptiform EEG activity. Issue 6 (June 1986) - Aminoff, M J; Simon, R P; Wiedemann, E
Abstract : Because of the known effects of seizures on plasma prolactin, the plasma prolactin levels were measured before and after generalised interictal epileptiform activity was provoked in the EEG in five epileptic patients. The findings were compared with those obtained in five normal subjects and three epileptic patients who were also exposed to flicker stimulation, but who did not develop a photoconvulsive EEG response. There was no significant difference in baseline prolactin values, and levels did not change with photic stimulation or in response to the presence of generalised epileptiform activity in the EEG.